Pengaruh Jumlah Kunjungan Dan Pengeluaran Wisatawan Mancanegara Terhadap Produk Domestik Regional Bruto (Pdrb) Provinsi Bali Tahun 1996-2012 - Dharma Yoga, I Gde Ary; Wenagama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
Tourismplays an important rolein increasingemployment, encourage theequitable distribution ofnational development, as well asplay a rolein alleviatingpoverty, which in turn willimprove thewelfare of the peoplein the province ofBali. This studyaims to determinehow theinfluence ofthe number of touristsandforeign touristsspendingto GDPbyusing path analysis. TestingResults of path analysis showed that the number of tourist arrivals affect the expenditure of foreign tourists , the number of tourists and foreign tourists spending simultaneous effect on GDP , is not directly affect the number of tourists visiting GDP by expenditure by tourists .
Keywords: foreign tourists; spending; GDP